Analysis of immunotherapy models in the context of cancer dynamics - Szymańska, Zuzanna (Zielona Góra: Uniwersytet Zielonogórski)
A basic mathematical model of the immune response when cancer cells are recognized is proposed. The model consists of six ordinary differential equations. It is extended by taking into account two types of immunotherapy: active immunotherapy and adoptive immunotherapy.
Keywords: dynamic systems; immune system; cancer; vaccination